Armenia in Public Perceptions: The Case of Armenian Youth - Marine Sargsyan (Slovo, 2020)
To download this paper, please click here This article is informed by a trip to Armenia and fieldwork in the capital city of Yerevan. Based on findings and evidence from fifty interviews conducted in Armenia and the diaspora, in conjunction with mobility research analysis, this paper explores the changes Armenian society has undergone since the 1990s and how shifts in world politics reflect on the country's reconnection with its European bonds. The general question is whether the new generation of Armenians identifies itself more closely with Russian or European society. To arrive at an answer, the article elaborates on Armenia's relations with Russia and the European Union, revealing the key factors that influence the orientation of Armenian society in contemporary history. The article, therefore, aims to contribute to understandings of past and present Armenian society, and the factors that affect and determine their cultural identityand foreign policy choice, as well as their sense of belonging.